Effect of an acute β-adrenergic blockade on exercise intensity corresponding to the lactate minimum - Denadai, B. S. [UNESP]; Balikian P., Jr [UNESP]; Neiva, C. M. [UNESP] (Taylor & Francis, 2000)
β-Adrenoreceptor blockade is reported to impair endurance, power output and work capacity in healthy subjects and patients with hypertension. The purpose of this study was to investigate the effect in eighth athletic males of an acute β-adrenergic blockade with propranolol on their individual power output corresponding to a defined lactate minimum (LM). Eight fit males (cyclist or triathlete) performed a protocol to determine the power output corresponding to their individual LM (defined from an incremental exercise test after a rapidly induced exercise lactic acidosis). This protocol was performed twice in a double-blind randomized order by each athlete first ingesting propranolol (80mg) and in a second trial a placebo, 120 minutes respectively prior to the test sequence. The blood lactate concentration obtained 7 minutes after anaerobic exercise (a Wingate test) was significantly lower after acute β-adrenergic blockade (8.6 ± 1.6mM) than under the placebo condition (11.7 ± 1.6mM). The work rate at the LM was lowered from 215.0 ± 18.6 to 184.0 ± 18.6 watts and heart rate at the LM was reduced from 165 ± 1.5 to 132 ± 2.2 beats/minute as a result of the blockade. There was a non-significant correlation (r = 0.29) between the power output at the LM with and without acute β-adrenergic blockade. In conclusion, since the intensity corresponding to the LM is related to aerobic performance, the results of the present study, are able to explain in part, the reduction in aerobic power output produced during β-adrenergic blockade.
Keywords: Adrenergic receptors; Anaerobic threshold; Lactate minimum; Propranolol; lactic acid; propranolol; adult; aerobic capacity; anaerobic threshold; athlete; beta adrenergic receptor blocking; bicycle ergometry; clinical trial; controlled clinical trial; controlled study; double blind procedure; exercise test; human; human experiment; lactate blood level; male; motor dysfunction; motor performance; normal human; randomized controlled trial